Implementasi Modified Enhanced Confix Stripping Stemmer pada Klasifikasi Fake News Covid-19 - Putri, Dyas Rahma; Dermawan, Budi Arif; Purnamasari, Intan (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Today's advances in technology and information make communication easier, so that the flow of information can quickly spread. The ease also allows anyone to upload anything on online platforms such as blogs, comments to news articles, social media, etc. that could lead to ambiguity of information or even lead to misleading information. Fake news is information that contains things that are uncertain or not a fact that actually happened. One of the popular news topics nowadays is about the covid-19 virus. This research evaluates the performance of Multinomial Naïve Bayes and Bernoulli Naïve Bayes in conducting fake news classifications related to covid-19. Beside that, we used Modified Enhanced Confix Stripping Stemmer in performing indonesian word standardization that has a variety of shapes and structures. The evaluation showed that Bernoulli Naïve Bayes model had the best performance than Multinomial Naïve Bayes, with the accuracy value of 91%, precision 0.93, recall 0.92, and f-1 score 0.92. In addition, the performance of Modified Enhanced Confix Stripping Stemmer (Modified ECS) algorithm is also perform very well in standardizing words (stemming) Indonesian language.